Chemical constituents of Phoebe grandis - (Lauraceae), (Nees) Merr. (Malaysian Journal of Science, 2000)
A Malaysian plant, Phoebe grandis (Nees) Merr. (Lauraceae) was studied for its chemical constituents. Four aporphine alkaloids were isolated from the stem bark, namely, boldine (1), norboldine (2), laurotetanine (3), and lindcarpine (4). ABSTRAK Satu spesis tumbuhan Malaysia, Phoebe grandis (Nees) Merr., (Lauraceae) telah dikaji kandungan kimianya. Empat aporfina alkaloid telah diperolehi daripada kulit batang iaitu boldina (1), norboldina (2), laurotetanina (3), dan lindkarpina (4). (Phoebe grandis, alkaloid)